2016
DOI: 10.1097/aog.0000000000001187
|View full text |Cite
|
Sign up to set email alerts
|

Occult Uterine Sarcoma and Leiomyosarcoma

Abstract: Morcellation is associated with decreased early survival of women with occult leiomyosarcomas. We could not accurately assess associations between power morcellation and 3-year survival as a result of small numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(24 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…We identified 11 studies 1012,1421 published since the FDA safety communications of sufficient quality and pertaining to our target population of women undergoing hysterectomy who might be subject to morcellation (Table). The number of subjects ranged from 808–241,114 and LMS rates ranged from 0–0.0032 (1:314).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 11 studies 1012,1421 published since the FDA safety communications of sufficient quality and pertaining to our target population of women undergoing hysterectomy who might be subject to morcellation (Table). The number of subjects ranged from 808–241,114 and LMS rates ranged from 0–0.0032 (1:314).…”
Section: Resultsmentioning
confidence: 99%
“…1012 Estimated LMS rates for women age <50 years ranged from 0.0011–0.0013. We selected 0.0012 as our <50-year-old base case.…”
Section: Resultsmentioning
confidence: 99%
“…However, 9 of 10 women with LMS were peri-or postmenopausal and over 50 years of age. The FDA emphasizes [13] that sarcomas in women undergoing surgeries due to presumed myomas approaches 2-3% in those over 60 years [19][20][21]. It should be highlighted that leyomyosarcomas often are unidentified before surgery as showed the data from the Cancer Registry of Norway [22], and in the Norwegian cohort, power morcellation of LMS has not led to reduced survival.…”
Section: Discussionmentioning
confidence: 99%
“…In our study the woman with LMS who underwent power morcellation is 1 of 3 women with the longest survival after LMS recognition from the case series. However, several new studies included in the recent FDA review [13] provide some evidence supporting an increased risk of relapse and decreased overall survival after power morcellation of LMS [19,23,24]. Conversely, another interpretation of the available data suggests that even intact removal of LMS has no advantage for mortality rate compared with power or any other type of morcellation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 34 cases (28%) incurred uterus morcellation, which may increase the risk of postoperative metastasis within three months. Recently, other studies also showed that laparoscopic surgery may lead to malignant planting in operating hole, abdominal and pelvic sarcoma 11 49 51 52 53 .…”
Section: Uterus Morcellation and Metastasis Of Uterine Sarcomamentioning
confidence: 99%